Oxyanions as inhibitors of chloride-induced crevice corrosion of Alloy 22 - Rincón Ortiz, Mauricio (2013)
Oxyanions were tested as inhibitors of the chloride-induced crevice corrosion of Alloy 22, at 90 °C. Nitrate was the most efficient inhibitor showing RCRIT = 0.2 for the two tested chloride concentrations. Sulphate showed RCRIT values of 1 and 2 in 0.1 mol/L and 1 mol/L NaCl solutions, respectively. Carbonate showed RCRIT = 1 while bicarbonate and carbonic acid did not show any inhibiting effect. Chromate and molybdate showed RCRIT = 0.5 in 0.1 mol/L NaCl solutions being less effective in 1 mol/L NaCl solutions. Tungstate produced a repassivation potential increase without reaching a complete inhibition.